Enhancing the SYSLAB system model with state - Grosu, Radu; Klein, Cornel; Rumpe, Bernhard 1967- (1996)
Abstract: "In this report, the SYSLAB system model is complemented in different ways: State-box models are provided through timed port automata, for which an operational and corresponding denotational semantics are given. Composition is defined for components modeled in the state-box view as well as for components modeled in the black-box view. This composition is well-defined for networks of infinitely many components. To show the applicability of the model, several examples are given."
Literaturverz. S. 40 - 42
Keywords: Mathematisches Modell; Mathematical models; Software engineering; System analysis; Systems engineering